DEVELOPMENT OF SUPERVISION IMPLEMENTATION ORIENTATION - Utami, Resti; Muhthadi, Muhthadi; Annur, Saipul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Teachers have a very important role and great responsibility in education which is a challenge when it comes to the quality of education today. So in this case, less professional teachers really need guidance and direction from other people or supervisors in solving the problems they face in order to achieve educational goals. This writing aims to discuss and understand the development of orientation for the implementation of supervision at this time. This research uses qualitative methods in the form of a literature study, with a descriptive approach. Data was collected through references from books and literature related to the challenges of developing orientation for the implementation of supervision at this time. The research results show that supervision is one of the principal's functions to improve the quality and professionalism of teachers in carrying out teaching. There are three approaches to educational supervision: clinical supervision, developmental, and differential.